Transcription factor MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene MoAUH1 to govern infectious growth via mitochondrial fusion/fission balance in Magnaporthe oryzae. (26th June 2020) - Xiao, Yuhan; Liu, Luping; Zhang, Ting; Zhou, Ruiwen; Ren, Yuan; Li, Xinrui; Shu, Haidong; Ye, Wenwu; Zheng, Xiaobo; Zhang, Zhengguang; Zhang, Haifeng
Summary: Mitochondrial quality and quantity are essential for a cell to maintain normal cellular functions. Our previous study revealed that the transcription factor MoMsn2 plays important roles in the development and virulence of Magnaporthe oryzae . However, to date, no study has reported its underlying regulatory mechanism in phytopathogens. Here, we explored the downstream target genes of MoMsn2 using a chromatin immunoprecipitation sequencing (ChIP‐Seq) approach. In total, 332 target genes and five putative MoMsn2‐binding sites were identified. The 332 genes exhibited a diverse array of functions and the highly represented were genes involved in metabolic and catalytic processes. Based on the ChIP‐Seq data, we found that MoMsn2 plays a role in maintaining mitochondrial morphology, likely by targeting a number of mitochondria‐related genes. Further investigation revealed that MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene ( MoAUH1 ) to control mitochondrial morphology and mitophagy, which are critical for the infectious growth of the pathogen. Meanwhile, the deletion of MoAUH1 resulted in phenotypes similar to the Δ Momsn2 mutant in mitochondrial morphology, mitophagy and virulence. Overall, our results provide evidence for the regulatory mechanisms of MoMsn2, which targets MoAUH1 to modulate its transcript levels, thereby disturbing the mitochondrial fusion/fission balance. This ultimately affects the development and virulence of M . oryzae .